Study on the coiler drive mechanism of the capacity increasing function. Issue 3 (February 2018) - Zhihong, Sun; Tianxin, Tang; Bocheng, Zhao; Yanting, Chen
In textile factories, the sliver can is used to deposit and transport sliver in the process of carding, combing and drawing. Increasing the capacity of the sliver can will reduce the frequency of changing the sliver can; hence, the working efficiency can be improved. A belt drive mechanism with the driven pulley eccentrically installed was developed in this study. This mechanism was used as the driving mechanism of the coiler, which has the effect of increasing the capacity of the sliver can. In this study, several commonly used methods of increasing the capacity of the sliver can were introduced first. Then, the equation of motion of the eccentric belt drive mechanism was established, and the law of motion of the driven eccentric pulley was calculated. Finally, the relationship between the eccentricity ( e ) of the driven eccentric pulley and the capacity increment ( δ ) of a sliver can was analyzed by utilizing the evaluation indicators of density of per sliver lap. The result indicates that with the increase in the value of eccentricity ( e ), the capacity increment ( δ ) of a sliver can also increases.